ELECTRODE MODIFICATION USING GOLD NANOSKIPE (AUNS) BY ELECTRODEPOSITION METHOD AND ITS APPLICATIOIN FOR ELECTROCHEMICAL-BASED DOPAMINE DETECTION - Rona Althof, Raih
Abnormality of dopamine levels in the body indicate various disorders such as Parkinson's, schizophrenia, and Alzheimer's disease. Early detection and prompt treatment can help reduce the impact on patients. Therefore, the development of dopamine detection sensors that are close to the patient (point-of-care testing) becomes important to help facilitate early detection and routine monitoring. One method that has the potential to be used is an electrochemical-based sensor considering that dopamine has a relatively good electrochemical activity. In addition, electrochemical-based sensors have the advantage of producing good sensitivity, easy to use, and fast measurements. However, optimization efforts are still needed to address some of the major challenges in detecting dopamine using electrochemical methods. These challenges include very low concentrations of dopamine in the body and the presence of other coexist organic materials which have the potential to interfere with dopamine detection signal responses. One of the commonly used methods is to modify the working electrode using a nanostructured metal material. Gold nanoparticles (AuNP) have been widely used in electrochemical-based sensors due to their attractive properties, such as very high active surface area, good biocompatibility, fast electron transfer, and good catalytic activity that allows detection of targets by non-enzymatic methods. In addition, nanostructured Au with different morphologies will provide different performance on electrochemical sensors. Au nanospike (AuNS) as one of the potential candidates for electrochemical applications has attracted a lot of attention due to its crystal orientation properties which can produce high electrocatalytic capability and increase active sites in electrochemical assays. To date, no research has been published regarding the electrochemical-based detection of dopamine using AuNS. In this study, the authors developed a simple AuNS electrodeposition on the electrode to be applied as a non-enzymatic detection sensor for dopamine. The electrodeposition method is used for the modification process because it is able to produce a varied morphology by controlling the electrodeposition parameters, including working potential, deposition time, and the addition of growth directing agent with a fast and simple process and homogeneous deposition results. Screen printed carbon electrode (SPCE) was chosen as the electrochemical electrode used because of its advantages, including the portaibility, simple, easy to use, relatively low-cost fabrication, so it has the potential for mass production. From the results of the study, it was found that the deposition parameter configuration that produces the most optimal modified electrode is electrodeposition using Constant Potential Amperommetry (CPA) with a working potential of ?0.2 V, for 1200s, and using a precursor concentration of 10 mM. AuNS produced with these parameters seems to have coated the entire surface of the carbon electrode homogeneously. With calculations obtained from electrochemical testing of H2SO4, the highest Electrochemical Surface Area (ECSA) was 0.716 cm2. As a dopamine sensor, AuNS-modified SPCE produced a sensitivity of 0.0556 ?A ?M-1 cm -2 with a linear range from a concentration of 0,2-50 ?M. In addition, AuNS-modified SPCE can selectively detect dopamine among other interfering analytes such as ascorbic acid, urea, and uric acid. These results indicate that AuNS-modified SPCE has the potential to be used as a dopamine detection sensor.